A molecular dynamics study of path-dependent grain boundary properties in nanocrystals prepared using different methods. (December 2021) - Sun, Hao; Béland, Laurent Karim
Abstract: Grain boundaries are thermodynamically unstable. Hence, their properties should be path-dependent: grain boundaries in nanocrystals prepared using different methods might exhibit different properties. Using molecular dynamics simulations, we investigated grain boundaries of different nanocrystals formed by quenching, solidification with pre-induced nucleation sites, and Voronoi tessellation, respectively. Some properties were found to be path-depend: the quenched model has lower boundary energy per atom, smaller boundary excess free volume per atom, and slower grain growth than the Voronoi model. We surmise that these differences are attributed to the abundant annealing twins in the quenched model. On the other hand, other properties are path-independent, such as Young's modulus, Poisson's ratio, and the ratio between grain boundary energy and excess free volume. The results of this study further the understanding of the structural-property relationship of nanocrystals and provide guidance to future simulation-based studies of nanocrystalline materials. Graphical abstract: Image, graphical abstract